Implementing gender transformative approaches in agriculture: A discussion paper for the European Commission - Wong, Franz; Vos, Andrea; Pyburn, Rhiannon; Newton, Julie (CGIAR Collaborative Platform on Gender Research, 2019)
Over the past 15 years, Gender Transformative Approaches (GTAs) have become prominent in the gender and development literature. For proponents, they are the source of both promise and inspiration, for their potential to have an impact on development outcomes as well as gender equality. We understand GTAs as ways to address the foundations of gender inequity and unequal power relations, with a focus on transforming gender relations to be more equitable. With this definition, GTAs are seen as distinct from, and complementary to, approaches to gender integration.